Eiders, nutrients and eagles: Bottom-up and top-down population dynamics in a marine bird_dataset - Morelli, Federico; Laursen, Karsten; Svitok, Marek; Benedetti, Yanina; Pape Møller, Anders (Zenodo, 2021)
The main objective of this long-term study (1978-2016) was to find the underlying factors behind the declining trends of eider Somateria mollissima in the Baltic/Wadden Sea. Specifically, we aimed at quantifying the bottom-up effect of nutrients, through mussel stocks, on reproduction and abundance of eider, and the top-down effects caused by white-tailed eagle Haliaeetus albicilla predation. Bottom-up effects increase marine primary productivity with subsequent effects on food availability for a major mussel predator. Top-down effects may also regulate eider populations because during incubation female eiders are vulnerable to predation by eagles. Our structural equation modelling explained a large percentage of the variance in eider abundance. We conclude that the Baltic/Wadden Sea eider population was regulated directly by white-tailed sea-eagle predation on incubating females and indirectly by the amount of nutrients in seawater affecting both mussel stocks and the breeding success of eiders, reflecting density dependence. These findings may explain the decreasing trend in the Baltic/Wadden Sea eider population during the last decades as an additive effect of top-down and bottom-up factors, and likely as an interaction between them. The dataset contains the metadata in the second excel sheet, describing each field. Additional information about the dataset could be asked to the corresponding author: E-mail: anders.moller@u-psud.fr